Implementasi Kebijakan Manajemen Mutu Dalam Penguatan Pendidikan Karakter Siswa di SMP Negeri 7 Muaro Jambi Dan SMP Negeri 11 Muaro Jambi - Zuliani, Atika; Chaifi, Luthfi Afif; Rambe, Aldi Syahputra; Indriyana, Dwi; Fitriani, Fitriani (Jurnal Ilmiah Dikdaya, 2023)
The aim of this research is to determine the implementation of quality management policies in strengthening character education at SMP N 7 Muaro Jambi and SMP N 11 Muaro Jambi. The method used is the case study method, a descriptive qualitative type through observation, interviews and document analysis. The results of the research show that SMP N 7 and SMP N 11 Muaro Jambi are almost the same in terms of educational quality, both in terms of vision and mission, programs, and implementation of the program itself. Meanwhile, the obstacle faced by these two schools is that there is no information system support for implementing systematic character education.